2012
DOI: 10.14194/ijmbr.139
|View full text |Cite
|
Sign up to set email alerts
|

Study on morbidity pattern among elderly in urban population of Mysore, Karnataka, India

Abstract: Background: Changes have been seen in the age structure of the population due to a steady rise in life expectancy and reduction in fertility. Aim: To know the morbidity pattern of the elderly in urban population of Mysore, delineate the common health conditions affecting the elderly and evaluate the differences in the morbidity pattern between the young old and old old. Material and Methods: This community based Cross sectional study was carried out at the field practice area of Urban Health Centre, JSS medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
41
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 4 publications
9
41
2
Order By: Relevance
“…8,11 Eye disease was present in 39.9% of elderly in the present study which was lower as compared to study by Shraddha et al 8 High prevalence of eye disorders was also reported by Goswami et al and Ajay K. et al 9,12 Prevalence of endocrine, nutritional & metabolic diseases was 28.2%. Prevalence of diabetes was 14.1% in present study which is similar to study by Shraddha et al 8 A higher prevalence of diabetes was found in studies by Sithara et al (33.2%). 13 In present study prevalence of anemia was 12.7% which is low as compared to study by Sharma et al where prevalence was 38.7%.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…8,11 Eye disease was present in 39.9% of elderly in the present study which was lower as compared to study by Shraddha et al 8 High prevalence of eye disorders was also reported by Goswami et al and Ajay K. et al 9,12 Prevalence of endocrine, nutritional & metabolic diseases was 28.2%. Prevalence of diabetes was 14.1% in present study which is similar to study by Shraddha et al 8 A higher prevalence of diabetes was found in studies by Sithara et al (33.2%). 13 In present study prevalence of anemia was 12.7% which is low as compared to study by Sharma et al where prevalence was 38.7%.…”
Section: Discussioncontrasting
confidence: 45%
“…Similar were the finding from other studies by Sijan Poudyal et al and Shraddha et al Sijan Poudyal et al reported 29.9% tooth decay, 10.3% mobile tooth in their study while Shraddha et al reported 23.7% prevalence of dental caries among elderly males. 8,10 Overall prevalence of musculoskeletal disorders in present study were 53.4%. Common diseases found in this group were arthritis (17.4%), backache (22.0%), and myalgia(13.4%).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In the present study majority (59.7%) of the elderly were females and 40.3% of elderly were males. Shraddha K et al 7 in their study conducted in Mysore, Karnataka found that 39.4% were males and 60.6% were females. Pooja Chauhan et al 8 in a study conducted in Venkatachalem village in Nellore district, AP found that 33.4% were males and 66.2% were females.…”
Section: Discussionmentioning
confidence: 94%